Implementation of resuscitative endovascular balloon occlusion of the aorta as an alternative to resuscitative thoracotomy for noncompressible truncal hemorrhage. Issue 4 (October 2015) - Moore, Laura J.; Brenner, Megan; Kozar, Rosemary A.; Pasley, Jason; Wade, Charles E.; Baraniuk, Mary S.; Scalea, Thomas; Holcomb, John B.
<x xml:space="preserve">Abstract</x> BACKGROUND Hemorrhage remains the leading cause of death in trauma patients. Proximal aortic occlusion, usually performed by direct aortic cross-clamping via thoracotomy, can provide temporary hemodynamic stability, permitting definitive injury repair. Resuscitative endovascular balloon occlusion of the aorta (REBOA) uses a minimally invasive, transfemoral balloon catheter, which is rapidly inserted retrograde and inflated for aortic occlusion, and may control inflow and allow time for hemostasis. We compared resuscitative thoracotomy with aortic cross-clamping (RT) with REBOA in trauma patients in profound hemorrhagic shock. METHODS Trauma registry data was used to compare all patients undergoing RT or REBOA during an 18-month period from two Level 1 trauma centers. RESULTS There was no difference between RT (n = 72) and REBOA groups (n = 24) in terms of demographics, mechanism of injury, or Injury Severity Scores (ISSs). There was no difference in chest and abdominal Abbreviated Injury Scale (AIS) scores between the groups. However, the RT patients had lower extremity AIS score as compared with REBOA patients (1.5 [0–3] vs. 4 [3–4], p < 0.001). Of the 72 RT patients, 45 (62.5%) died in the emergency department, 6 (8.3%) died in the operating room, and 14 (19.4%) died in the intensive care unit. Of the 24 REBOA patients, 4 (16.6%) died in the emergency department, 3 (12.5%) died in the operating room, and 8 (33.3%) died in the intensive care unit. In comparing location of death between the RT and REBOA groups, there were a significantly higher number of deaths in the emergency department among the RT patients as compared with the REBOA patients (62.5% vs. 16.7%, p < 0.001). REBOA had fewer early deaths and improved overall survival as compared with RT (37.5% vs. 9.7%, p = 0.003). CONCLUSION REBOA is feasible and controls noncompressible truncal hemorrhage in trauma patients in profound shock. Patients undergoing REBOA have improved overall survival and fewer early deaths as compared with patients undergoing RT. LEVEL OF EVIDENCE Therapeutic study, level IV.